2010
DOI: 10.1166/jnn.2010.1741
|View full text |Cite
|
Sign up to set email alerts
|

<I>In Vitro</I> Phototoxicity of Liposomes and Nanocapsules Containing Chloroaluminum Phthalocyanine on Human Melanoma Cell Line

Abstract: In this study, the photodynamic action of liposomes (LP) and nanocapsules (NC) containing Chloroaluminum phthalocyanine (CIAIPc), on the human melanoma cell (WM 1552C), was assessed. The light source was setup at 672 nm, which corresponds to the maximum absorption wavelength of the CIAIPc. Both colloidal carriers presented size in nanometric scale as well as negative zeta potential. The cellular damage was light dose dependent ranging from 30% of cell death at 70 mJ x cm-2 to 90% of death at 700 mJ x cm(-2). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 0 publications
0
21
0
10
Order By: Relevance
“…The results of our particle size analysis indicated that the mean size of the particles used in our system is in this adequate nanometric range (average diameter of 8 nm). The surface charge or zeta potential (ζ) is the electrokinetic potential formed by an ionic double layer that is susceptive to a voltage difference in millivolts [40]. The measurement of ζ allows predictions of the stability of colloidal aqueous dispersions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our particle size analysis indicated that the mean size of the particles used in our system is in this adequate nanometric range (average diameter of 8 nm). The surface charge or zeta potential (ζ) is the electrokinetic potential formed by an ionic double layer that is susceptive to a voltage difference in millivolts [40]. The measurement of ζ allows predictions of the stability of colloidal aqueous dispersions.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular culture was accomplished as described by Barbugli et al 14 The cells were treated with five formulations (1 ¼ drug-free nanocapsule þ ionic magnetic fluid at 5 Â 10 9 particle/ml; 2 ¼ Selol-loaded nanocapsules at 100 lg/ml; 3 ¼ Selol-loaded nanocapsule at 25 lg/ ml þ ionic magnetic fluid at 1.25 Â 10 9 particle/ml; 4 ¼ Selolloaded nanocapsule at 50 lg/ml þ ionic magnetic fluid at 2.5 Â 10 9 particle/ml; and 5 ¼ Selol-loaded nanocapsule at 100 lg/ml þ ionic magnetic fluid at 5 Â 10 9 particle/ml) for 3 h in an incubator (5% CO 2 , 37 C, humidified atmosphere). Subsequently, the medium with formulations was removed.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, phthalocyanines (Pc) have been under investigation as promising second-generation photosensitizers, not only for PDT, but also for other applications. Because of their strong red-shifted absorption band, associated with their photophysical response, they are well suited to take advantage of maximal tissue penetration and low-light scattering properties of organelles and tissue at the ideal phototherapeutic window (600-800 nm).For instance, aluminum chloride phthalocyanine presents an intense absorption peak at 670 nm, and, therefore, diode laser operating at this wavelength is required [30,31].…”
Section: Interaction Of Light In the Skinmentioning
confidence: 99%